A case report on the function(s) of the 'mercury jar': Fort Canning, Singapore, in the 14th century. (July 2016) - Wong, Sharon Wai-yee
Abstract: The 'mercury jar' is a distinctive type of Chinese ceramics unearthed from the Fort Canning site in Singapore, dating to the 14th century. This case report will discuss the type, quantity, and distribution of the 'mercury jar' found at this site; providing a preliminary comparison with its production sites at Cizao Kilns, Jinjiang, Fujian Province, China and other Southeast Asian sites. This report also serves to advance topics for further discussion on the possible original function(s) of the jar as a grain wine or mercury container, and on the major consumers of the 'mercury jar', from members of the upper classes to state officials during this period.